The Dilemma of Implementing the Public Service Agency (BLU) Policy in Islamic State Higher Education Institutions (PTKIN) in Aceh: Between Institutional Autonomy and Lecturer Welfare - Yusaini Yusaini (International Journal of Education, Language, and Social Science, 2026)
This study aims to analyze the paradox of institutional autonomy and internal conflicts of interest between university leaders and lecturers in the implementation of the Public Service Agency (BLU) system at Islamic State Higher Education Institutions (PTKIN) in Aceh. The novelty of this study lies in its examination of how financial autonomy under the BLU scheme simultaneously shapes institutional governance and generates internal social tensions within relatively small Islamic higher education institutions, an issue that has received limited scholarly attention. This research employed a descriptive qualitative design using a case-study orientation to explore the institutional and social dynamics of BLU implementation. Data were collected through semi-structured interviews, observations, documentation, and closed-ended questionnaires used as supporting instruments to strengthen data triangulation rather than for quantitative hypothesis testing. Data were analyzed using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing, while the trustworthiness of the findings was ensured through source and technique triangulation. The findings indicate that BLU implementation in PTKINs in Aceh remains constrained by a high dependence on student tuition fees (UKT/SPP) and limited optimization of alternative institutional revenue sources. Furthermore, financial autonomy has contributed to differing perceptions of welfare and resource distribution between structural leaders and non-structural lecturers, creating internal conflicts of interest that influence institutional cohesion. This study contributes to the literature on higher education governance by demonstrating that the success of BLU implementation depends not only on financial autonomy but also on equitable governance and participatory institutional management. It concludes that the implementation of the BLU system in smaller PTKINs requires a contextual, transparent, and inclusive governance model to strengthen institutional sustainability while minimizing financial disparities and internal social conflict